Composition and changes of blood microbiota in adult patients with community-acquired sepsis: A pilot study from bench to bedside - Szabó, Bálint Gergely; Kiss, Rebeka; Makra, Nóra; Pénzes, Kinga; Vad, Eszter; Kamotsay, Katalin; Szabó, Dóra; Ostorházi, Eszter (Frontiers in Cellular and Infection Microbiology, 2022)
Background Characteristics of the blood microbiota among adult patients with community-acquired sepsis are poorly understood. Our aim was to analyze the composition of blood microbiota in adult patients with community-acquired sepsis, and correlate changes with non-septic control patients. Methods A prospective observational study was carried out by including adult patients hospitalized for community-acquired sepsis at our center between January and November 2019, by random selection from a pool of eligible patients. Study inclusion was done on the day of sepsis diagnosis. Community acquisition was ascertained by a priori exclusion criteria; sepsis was defined according to the SEPSIS-3 definitions. Each included patient was matched with non-septic control patients by age and gender in a 1:1 fashion enrolled from the general population. Conventional culturing with BacT/ALERT system and 16S rRNA microbiota analysis were performed from blood samples taken in a same time from a patient. Abundance data was analyzed by the CosmosID HUB Microbiome software. Results Altogether, 13 hospitalized patients were included, 6/13 (46.2%) with sepsis and 7/13 (53.8%) with septic shock at diagnosis. The most prevalent etiopathogen isolated from blood cultures was Escherichia coli, patients mostly had intraabdominal septic source. At day 28, all-cause mortality was 15.4% (2/13). Compared to non-septic control patients, a relative scarcity of Faecalibacterium, Blautia, Coprococcus and Roseburia genera, with an abundance of Enhydrobacter, Pseudomonas and Micrococcus genera was observed among septic patients. Relative differences between septic vs. non-septic patients were more obvious at the phylum level, mainly driven by Firmicutes (25.7% vs. 63.1%; p<0.01) and Proteobacteria (36.9% vs. 16.6%; p<0.01). The alpha diversity, quantified by the Chao1 index showed statistically significant difference between septic vs. non-septic patients (126 ± 51 vs. 66 ± 26; p<0.01). The Bray-Curtis beta diversity, reported by principal coordinate analysis of total hit frequencies, revealed 2 potentially separate clusters among septic vs. non-septic patients. Conclusion In adult patients with community-acquired sepsis, specific changes in the composition and abundance of blood microbiota could be detected by 16S rRNA metagenome sequencing, compared to non-septic control patients. Traditional blood culture results only partially correlate with microbiota test results.